Basal-Supported Oral Therapy with Sitagliptin Counteracts Rebound Hyperglycemia Caused by GLP-1 Tachyphylaxis - Shu Meguro; Toshihide Kawai; Tomohiro Matsuhashi; Motoaki Sano; Keiichi Fukuda; Hiroshi Itoh; Yoshihiko Suzuki (International Journal of Endocrinology)
Introduction. Treatment with a glucagon-like peptide 1 (GLP-1) analog fails in some patients due to rebound hyperglycemia caused by tachyphylaxis (GLP-1 tachyphylaxis). We investigated the efficacy of basal-supported oral therapy (BOT) with insulin glargine and sitagliptin for counteracting GLP-1 tachyphylaxis. Materials and Methods. The subjects were 12 men and 3 women aged 59.9±10.0 years who had been treated with GLP-1 analogs. All of them had developed rebound hyperglycemia caused by GLP-1 tachyphylaxis. Their GLP-1 analog-based therapy was switched to BOT with insulin glargine plus sitagliptin and other medications. The primary outcomes were whether switching of therapy was associated with a change of hemoglobin A1c (HbA1c) and whether weight gain occurred. Results. Baseline HbA1c was 8.0±0.9%. It decreased to 7.3±0.9% at 3 months after switching (P<0.01) and to 7.2±0.9% at 4 months (P<0.05). Weight gain was 1.1 kg after 1 month (P<0.01) and 2.3 kg after 5 months (P<0.01). Conclusion. Switching to BOT with insulin glargine and sitagliptin improved glycemic control. The significant decrease of HbA1c demonstrated that this combination can counteract deterioration of glycemic control due to rebound hyperglycemia secondary to GLP-1 tachyphylaxis. However, weight gain remains a problem.